The Future of Conferences: Towards an Ongoing, Reflexive Practice - An Invitation for Debate - Csobod, Judit (Jazz Research Journal, 2023)
In this first piece of our new series, our contributors address issues around an important element of our academic infrastructure, namely conferences. We are all too familiar with the frustrations that emerge from outdated conference formats, the real-time manifestations of hierarchies, the lack of time and space for discussion in the official programs, the pricey and environmentally excessive travel and accommodation arrangements, and the overwhelmingly long days and exasperating parallel sessions. Although the pandemic presented us with a chance to rethink many of our business-as-usual practices, the disappointment of returning to post-COVID conferences that do not reflect any of these discussions and visions for the post-lockdown future is palpable. Returning to our manifesto mission, contemplating approaches for creating places for inclusivity, accessibility, kindness and safe spaces for debate, we have asked four colleagues to share their experiences at academic and non-academic conferences as a means to reinvigorate these discussions and (potentially) renew our interest in making positive and sustainable changes in how to network and we share our research.